2014
DOI: 10.5152/tftrd.2014.31032
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Nosocomial Urinary Tract Infections with Spinal Cord Injury Patients in a Rehabilitation Setting

Abstract: Objective: To define the distribution and antibiotic susceptibility of nosocomial urinary tract infections (NAUTIs) in patients with spinal cord injury (SCI). Material and Methods: Records of the spinal cord injured patients were reviewed for NAUTIs between 2008 and 2010. Antibiotic resistance rates and factors that might affect urinary tract infection susceptibility were investigated retrospectively. Results: The data of 276 patients were included, of whom 159 were acute SCI patients and 117 were chronic SCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The difference between acute and chronic SCI patients in rates of NAUTI (ASB and SUTI) in terms of bladder drainage method was statistically insignificant. Susceptibility ratio for E.coli in patients of acute and chronic SCI using Foley catheter was very low; however it was not that low in patients using clean intermittent catheterization 22 . Another study had 91 SCI patients with 53 males and 38 females having mean age of of 45.29 ± 17.87 years.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The difference between acute and chronic SCI patients in rates of NAUTI (ASB and SUTI) in terms of bladder drainage method was statistically insignificant. Susceptibility ratio for E.coli in patients of acute and chronic SCI using Foley catheter was very low; however it was not that low in patients using clean intermittent catheterization 22 . Another study had 91 SCI patients with 53 males and 38 females having mean age of of 45.29 ± 17.87 years.…”
Section: Discussionmentioning
confidence: 84%
“…Also, it showed that type of bacteria and its response to various antibiotics can be different in different settings. Also, bacteria may acquire resistance to the antibiotics being used in a particular set up 7 .…”
Section: Introductionmentioning
confidence: 99%